Classification and Management of Donor-Site Wound Complications in the Profunda Artery Perforator Flap for Breast Reconstruction - Cho, Min-Jeong; Teotia, Sumeet S.; Haddock, Nicholas T. (Journal of Reconstructive Microsurgery, 2020)
Background Profunda artery perforator (PAP) flap breast reconstruction has emerged as a popular choice for patients who are not optimal candidates for autologous breast reconstruction using abdominal-based techniques such as the deep inferior epigastric perforator flap. Despite increased utilization of PAP flaps, there are no previous studies on the donor-site morbidity. In this study, we present risk factors, classification of thigh wounds, and our management of donor-site wounds.Methods Retrospective review of 69 patients who underwent PAP flap from 2013 to 2016 was performed. Demographic, patient characteristic, and flap data were collected. Postoperative photographs of donor sites were reviewed, and the wounds were classified into three types: type I—normal wound, type II—minor scab, and type III—dehiscence.Results Of the 69 patients (130 flaps), there were 13 patients (17 flaps) with wound dehiscence (13%), 8 patients with cellulitis (8.5%), 2 patients with seroma (3%), and 1 patient with hematoma (1.5%). The patients with wound dehiscence had statistically higher body mass index (BMI) (29.2 vs. 26.5) with p-value < 0.05 than the patients without wound complications. These patients had higher flap weight (514 vs. 439.7 g), were older (50.8 vs. 48.6 years old), and had a higher chance of being a diabetic (6 vs. 2%), but statistical significance was not achieved. The patients with dehiscence were managed with local wound care (63%), wound vacuum (26%), and operative intervention (11%).Conclusion Our study shows that BMI plays a significant role in the development of postoperative thigh wounds, and all wounds occurred at the medial thigh. However, the majority of the study population did not require any intervention, and revision of scar using the posterior thigh advancement flaps can be used to improve the gluteal aesthetics. We believe findings from our study can help plastic surgeons to counsel and assist patients who will undergo breast reconstruction with a PAP flap.
Keywords: profunda artery perforator flaps; breast reconstruction; wound dehiscence; management; classification